CASE OF XANTHOGRANULOMATOUS OOPHORITIS - Khan, Bushra; Aziz, Aliya Begum; Ahmed, Rashida (Journal of Ayub Medical College Abbottabad, 2017)
Xanthogranulomatous inflammation is characterized by destruction of the tissues of the organ involved and replacement by chronic inflammatory cells such as lymphocytes, plasma cells, occasional neutrophils with or without multinucleated or Touton giant cells. Exact aetiology is not known but the theory of infection with organisms like Proteus, E coli, and Bacteroides fragilis is most popular. Xanthogranulomatous inflammation of the female genital tract is not common and usually involves the endometrium, however, xanthogranulomatous inflammation of the ovaries is a rare entity. Keywords: Lipid laden macrophages; Xanthogranuloma; Chronic inflammation; Oophoritis; Ovaries